O cotidiano do ser adolescente que cumpre medida sócioeducativa: desvelando possibilidades assistenciais de enfermagem - Carmo, Dilce Rejane Peres do (2010)
This research was developed in a phenomenological approach through Martin Heidegger´s line of thinking, aiming to understand the adolescent-being life experience while captive in the Semi-Freedom Socioeducational Attention Center. The scenario of this research is the Socioeducational Attention Foundation, in Santa Maria, RS, Brazil. It began after it was authorized by the Foundation and the Universidade Federal de Santa Maria Ethics Committee. For the data production a phenomenological interview was applied to nine institutionalized teenagers. Through a comprehensive analysis the results show that living under the socioeducative measure means for the teenager a prison, something bad and that he must pay for his deeds. He recognizes that he has done wrong. He knows that he is not in the penitentiary system because of his age and he recognizes that he has lost his teenagehood. In the institution he goes to school to learn something, to get a job. He has trouble living among his street rivals and dealing with the institutional agents´ authority and in an unequal system. He valorizes his family, father, mother, brothers, cousins, uncles, son and girlfriend, which his half-freedom allows him to have. In the interpretative analysis, the adolescent-being day-by-day amidst the socioeducative measure reveals ways to be, which expresses impersonality. Absorbed by the system´s routine he keeps busy, and shows that he is thrown in that which is determined and where he belongs. It implies an effort on living among others, which constitutes a special way of being in the world, which is totally absorbed by the world and by the presence of the others in the impersonal. In keeping occupied and in decadence he shows that he needs help from the nursing and the socioeducative measure through the transdisciplinar work and by the strengthening of a social network support, aiming his re-insertion through the co-responsibility of his family, community and State. It brings to light a care that makes possible the recovery of the choice, that can give back the singularity of being.